Analisis Tingkat Kesehatan Bank Berdasarkan Pendekatan RGEC Pada Bank BUMN Periode 2013 - 2017 - Faradina Inda Wardhani; Muliani Muliani (Jurnal Ekonomi STIEP, 2019)
This study aims to determine the health level of state-owned banks listed onthe BEI in 2013-2017. Variable used in this study is the ratingof bank health by using RGEC formula. Based on data collection methods used in this studyis data collection techniques by way of documentation. The documentation used isin the form of their respective financial statements and self assessment. Theresultsof the research on the health status of state-owned banks listed on the BEI in2013-2017 show that Bank Negara Indonesia (BNI), Bank Rakyat Indonesia (BRI)and Bank Mandiri get PK- 1 or "Very Healthy" while Bank Tabungan Negara (BTN)get PK – 2 or "Healthy".